The automotive body volume II: system design - Morello, Lorenzo; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
The Automotive Body consists of two volumes. The first volume produced the needful cultural background on the body; it described the body and its components in use on most kinds of cars and industrial vehicles: the quantity of drawings that are presented allows the reader to familiarize with the design features and to understand functions, design motivations and fabrication feasibility, in view of the existing production processes. The purpose of this second volume is to explain the links which exist between satisfying the needs of the customer (either driver or passenger) and the specifications for vehicle design, and between the specifications for vehicle system and components. For this study a complete vehicle system must be considered, including, according to the nature of functions that will be discussed, more component classes than considered in Volume I, and, sometimes, also part of the chassis and the powertrain. These two books about the vehicle body may be added to those about the chassis and are part of a series sponsored by ATA (the Italian automotive engineers association) on the subject of automotive engineering; they follow the first book, published in 2005 in Italian only, about automotive transmission. They cover automotive engineering from every aspect and are the result of a five-year collaboration between the Polytechnical University of Turin and the University of Naples on automotive engineering.
7 INTRODUCTION TO VOLUME II -- 8 FUNCTIONS AND SPECIFICATIONS -- 8.1 Transportation statistics -- 8.2 Vehicle functions -- 8.3 Requirements measurement -- 8.4 Regulations -- 9 ERGONOMICS AND PACKAGING -- 9.1 Hints on Physiology -- 9.2 Manikins for interior packaging -- 9.3 Hints of occupants positioning -- 9.4 Pedals functionality and positioning -- 9.5 Interior packaging -- 9.6 Seat characteristics -- 9.7 Accessibility -- 9.8 Commands reach -- 9.9 Loading and unloading -- 9.10 Visibility -- 10 CLIMATIC COMFORT -- 10.1 Physiology outline -- 10.2 Passenger compartment energy balance -- 10.3 HEVAC System design and testing -- 11 NOISE, VIBRATION, HARSHNESS -- 11.1 Sensitivity to noise -- 11.2 Sources of noise and vibration -- 11.3 Dynamic behavior of the car body and modal analysis -- 11.4 Engine suspension -- 11.5 Acoustic transmission and insulation -- 12 STRUCTURAL INTEGRITY -- 12.1 Internal and external loads -- 12.2 Behavior of thin wall structures -- 12.3 Simplified structural models -- 12.4 Numerical models for structural analysis -- 12.5 Measurement of the car body stiffness -- 13 PASSIVE SAFETY -- 13.1 Biomechanics -- 13.2 Simplified models for crash -- 13.3 INTRODUCTION ON IMPACT ENERGY ABSORBERS -- 13.4 FRONT STRUCTURE CONFIGURATION -- 13.5 TESTING ON VEHICLES -- 13.6 IMPACT TESTS EQUIPMENT -- 13.7 NON LINEAR FEM ANALYSIS -- 13.8 Simplified models for crash -- 13.9 INTRODUCTION ON IMPACT ENERGY ABSORBERS -- 13.10FRONT STRUCTURE CONFIGURATION -- 13.11TESTING ON VEHICLES -- 13.12IMPACT TESTS EQUIPMENT -- 13.13NON LINEAR FEM ANALYSIS -- References -- INDEX.
Electronic reproduction.
Keywords: Automobiles -- Bodies -- Design and construction; Electronic books